Tinjauan Soal Penilaian Tengah Semester Pada Materi Matematika Berdasarkan Tingkat Kognitif Peserta Didik Di Sekolah Dasar - Jamaludin Jamaludin; Epon Nur’aeni; Yusuf Suryana; Ika Fitri Apriani (STKIP Andi Matappa Pangkep, 2022)
The purpose is to reveal the assessment questions to review the percentage and suitability of that. The method used is a descriptive method of document analysis. The object is the mid-semester assessment of math class VI in one of the elementary schools in Cibeureum District, Tasikmalaya City. Data collection techniques through interviews and documentation studies. The instrument used is guidelines analysis sheets, a rubric / matrix based on Bloom's taxonomy and interview guidelines. Data analysis includes the stages of data collection, reduction, presentation and drawing conclusions. The results revealed that 80% questions were in accordance with the operational verb indicators at the cognitive level of C2 (understanding). The percentage of questions obtained is 100% of the total questions at the cognitive level C2 (understanding). From the responses of educators, it was obtained: (1) not paying attention to the preparation of learning assessments based on cognitive levels and tending to refer to operational verbs at the level of basic competence, (2) teacher tend to be have difficulty solving problems based on Higher Order Thinking Skills in mid -semester assessments.